(3RHOI GdacQI aj JGQjN GdgLQIs - (3GdCejQ Qcf GdOjf HjHQS GdefUhQi GdOhGOGQi GdeUQj,J (B725 (3g` s ((3GHf cHjQ GdfUQGfi s)
(3ChdgG (B:s
(3jHJOF HGHJOGA GdOhdI GdYHGSjI ai SfI (B132 s
(3BNQgG (B:s
(3jfJgi Edi NdGaI GdeSJYjf s
(3hgh JGQjN cHjQ eQJH Ydi GdSffs
(3fSNI eUhQI Yf LGeYI ChHSGdGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B80s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B150 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs